Danger due to the translocation of nanoparticles in soil: mathematical modeling. Issue 1 (October 2015) - Lisyuk, Yu; Vorobyev, S; Izerskaya, L; Morgalev, Yu
Abstract: A necessary step was taken towards the formation of a migration model of nanoparticles (NPs) from the surface deep into the soil, taking into account the frequency of precipitation and the processes of adsorption and desorption which occur in the soils. An equation for migration of nanoparticles in soil is proposed. A method of obtaining the averaged equations for long-term migration of NPs in the soil profile has been developed. Similarly, partial differential equations may be obtained which describe more complex models, for example, including capillary phenomena, etc. The obtained equations allow the use of integral transformations in order to find solutions. The model can be used to plan natural experiments in different types of soils.